The process of differentiation during spermatogenesis in bees (Hymenoptera, apidae) - Da Cruz-Landim, Carminda [UNESP]; Beig, Darvin [UNESP]; De Moraes, Regina L. M. Silva [UNESP] (Firenze University Press, 1980)
The structural changes during spermatogenesis were studied on developing spermatogonia in drone testes of seven species of bees including the honeybee Apis mellifera and six other stingless bees. In view of the uniqueness of the spermatogenic process in the honeybee haploid drone this study was made in order to compare the events characteristic of spermatogenesis in other bees. Based on the results obtained we conclude that usually the primary spermatocytes undergo an abortive first meiotic division and further an unequal division of the secondary -spermatocyte. This mechanism in associated to the formation of centriolar blebs. The main difference observed is concerned with the premeiotic cell division (4 in Apis and 5 ones in other bees). The poliploidy seems to have no effect on the chromosome distribution in meiotic cells even if occurs the pairing of the homologous. Very few interespecific variations during spermatid differentiation were confirmed. © 1980 Taylor & Francis Group, LLC.